Role of Social Support in Reducing the Severity of Menopausal Symptoms among Women Living in Rural Mysuru, Karnataka: An Analytical Cross-sectional Study - K. L Divya; K. Nimithamohan; Anil S. Bilimale; Kiranmayee Muralidhar; Karl Krupp; Purnima Madhivanan (Wolters Kluwer Medknow Publications, 2024)
Introduction: Menopause is an unspoken and unaddressed aspect of a women's life, surrounded by many myths and taboos within the Indian context. Although a majority of menopausal women experience moderate to severe symptoms that can affect their physical, emotional, mental, and social well-being, there is poor health literacy as well as health-seeking behavior among them. The importance of social support, especially at a difficult time like menopause, is bound to minimize the severity of menopausal symptoms. Objectives: The objective is to assess the severity of menopausal symptoms among women living in rural communities of Mysuru district, and to examine the relationship of perceived social support during menopausal transition to severity of the symptoms. Materials and Methods: Between May 2022 and December 2022, a cross-sectional study was conducted among 250 women living in rural communities of Mysuru district, Karnataka. An interviewer-administered survey in Kannada was used to record the severity of menopausal symptoms and associated determinants after completion of informed consent process. Results: The average age of study participants was 50.9 (standard deviation [SD] ±4.6) years. While 77.2% were married, 20.8% were widows. About half (53.6%) belonged to lower socioeconomic class and another 28% belonged to middle class. The mean age at menopause was 47.6 (SD ± 4.24) years; 56.8% reported experiencing moderate-to-severe symptoms; 75.6% reported high social support while 24.4% of women low-to-medium social support. The odds of experiencing moderate-to-severe menopause symptoms were 4.51 (95% confidence interval: 2.337-8.690) times higher among women who received low-to-medium social support as compared to those with high social support. The social support obtained was directly proportional to socioeconomic status and living with spouse. Conclusion: The health system should emphasize the role of social support while counseling postmenopausal women. There is a dire need for both community and physician education programs on the social and medical needs of postmenopausal women.